2023
DOI: 10.1109/access.2023.3239894
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Characteristics for Hand-Vein Biometric Recognition: Analysis and Exploitation

Abstract: In recent years, vein-based biometric recognition has received ever-increasing attention from both academia and industry, due to the advantages it offers over traditional biometric traits such as fingerprint, iris, and face. Nonetheless, some issues related to the use of vein biometrics still need to be investigated and understood. Specifically, in this study, we speculate about the gender-related variations in vein patterns, and their effects on biometric verification performance. An analysis on the feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, to the best of our knowledge, few works in the literature evaluate gender-and age-recognition tasks on vein pattern images. Particularly, we have only found four works for palm vein images [6,11,15,16], whereas other authors have experimented with dorsal hand images [12,[37][38][39] and the finger veins [11,40].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…However, to the best of our knowledge, few works in the literature evaluate gender-and age-recognition tasks on vein pattern images. Particularly, we have only found four works for palm vein images [6,11,15,16], whereas other authors have experimented with dorsal hand images [12,[37][38][39] and the finger veins [11,40].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, [6] indicated that vein-topology-related features, such as the vein pattern gradient, can provide insights into gender information. Additionally, Kuzu et al [11] used gender-specific features for palm vein recognition. Moreover, the visualization of palm veins is influenced by age and body build due to variations in light intensity caused by differences in hemoglobin levels, water content in the blood, and skin properties [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of soft biometrics that are extracted from a human body include height, weight, age, eye color, etc. Few studies have shown that when combining soft biometrics with traditional (hard) biometrics, these traits can have practical usage and significant importance in improving recognition performance [15][16][17].…”
Section: Introductionmentioning
confidence: 99%